(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
This article explores the relationships between fashion, glamour, celebrity, and Canadian literature, focusing specifically on Toronto, Canada. I argue for the value of “reading glamour” into Toronto’s literature by examining how glamour provides a socio-cultural insight into character and plot development and, moreover, elevates the character of the city itself. No doubt certain authors conjure up a glamorous cachet with their coterie of bohemian intellectual and literary salons but the writing itself rarely approaches the same level of glamorous celebration. However, reading glamour—that is, following Brown, tracing the language and grammar of glamour as a literary form linked to modern mass culture—extends the potential for literary and cultural expression of the text. As Gundle and Castelli argue, glamour is typically associated with the urban and cosmopolitan, and this paper explores how Toronto has historically engaged with its own sense of burgeoning celebrity, fashion, and glamour. By focusing on the work of Phyllis Brett Young’ s The Torontonians(1960), I examine how glamour as a corollary to fashion challenges preconceptions of “Toronto the Good,” not only within the local urban imaginary but also on national and global levels.